2000
DOI: 10.1128/iai.68.7.4255-4263.2000
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Trafficking ofBrucella abortusin J774 Macrophages

Abstract: Brucella abortus is a facultative intracellular bacterium capable of surviving inside professional and nonprofessional phagocytes. The microorganism remains in membrane-bound compartments that in several cell types resemble modified endoplasmic reticulum structures. To monitor the intracellular transport of B. abortus in macrophages, the kinetics of fusion of phagosomes with preformed lysosomes labeled with colloidal gold particles was observed by electron microscopy. The results indicated that phagosomes cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 27 publications
8
119
0
4
Order By: Relevance
“…counting showed no difference with the wild-type strain. This is not very surprising since previous data reported proliferation outside ER-derived compartments (Arenas et al, 2000;Bellaire et al, 2005 (ERGIC) or autophagosomes, as proposed previously (Pizarro-CerdĂĄ et al, 1998). ERGIC would be an interesting candidate since it was already shown that (i) Rab2, a Rab GTPase associated with ERGIC, is recruited on the BCVs and that (ii) the GAPDH/COPI/Rab2/PKC i/l complex, involved in retrograde transport between the ER and Golgi apparatus, is required for bacterial proliferation (Fugier et al, 2009).…”
Section: Discussionsupporting
confidence: 56%
“…counting showed no difference with the wild-type strain. This is not very surprising since previous data reported proliferation outside ER-derived compartments (Arenas et al, 2000;Bellaire et al, 2005 (ERGIC) or autophagosomes, as proposed previously (Pizarro-CerdĂĄ et al, 1998). ERGIC would be an interesting candidate since it was already shown that (i) Rab2, a Rab GTPase associated with ERGIC, is recruited on the BCVs and that (ii) the GAPDH/COPI/Rab2/PKC i/l complex, involved in retrograde transport between the ER and Golgi apparatus, is required for bacterial proliferation (Fugier et al, 2009).…”
Section: Discussionsupporting
confidence: 56%
“…is different in HeLa cells and macrophages. Indeed, results obtained on intracellular trafficking of B. abortus in J774 macrophages report that only a few bacteria are localized in autophagosomes and ER-like structures (55). However, partial analysis of the virulome of B. melitensis has been performed in HeLa cells, and some amino acid biosynthesis pathways have been shown to be necessary (6,56).…”
Section: Role Of Smooth Lipopolysaccharide In Intracellular Multiplicmentioning
confidence: 99%
“…Phagosomes containing virulent B. abortus are reluctant to fuse with lysosomes, whereas those with dead B. abortus colocalize with endocytic compartments in the early stage of infection in macrophages (Arenas et al, 2000). To test the ability of B. abortus to target properly within macrophages early in infection, interaction of the mutants with the endocytic pathway was quantified by immunofluorescence localization of LAMP-1, a membrane protein of late endosomes and lysosomes (Chen et al, 1988).…”
Section: Effects Of Disruption Of the Spot Gene In Vitro And In Vivomentioning
confidence: 99%